If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6 + -3(6 + 4x) = -24 + -2x -6 + (6 * -3 + 4x * -3) = -24 + -2x -6 + (-18 + -12x) = -24 + -2x Combine like terms: -6 + -18 = -24 -24 + -12x = -24 + -2x Add '24' to each side of the equation. -24 + 24 + -12x = -24 + 24 + -2x Combine like terms: -24 + 24 = 0 0 + -12x = -24 + 24 + -2x -12x = -24 + 24 + -2x Combine like terms: -24 + 24 = 0 -12x = 0 + -2x -12x = -2x Solving -12x = -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -12x + 2x = -2x + 2x Combine like terms: -12x + 2x = -10x -10x = -2x + 2x Combine like terms: -2x + 2x = 0 -10x = 0 Divide each side by '-10'. x = 0.0 Simplifying x = 0.0
| 91=-7(2n-7) | | -5*(1/9+x)=0 | | 114=(x+2)15-3x | | -(4y+3z-4)= | | x+1(2)+x(2)=14 | | 2x+8=8+2x | | 18=c+5/2 | | (x+2)(x-1)(x+1)=0 | | -5a+2a=12-15 | | 15-2(2w+1)=7w-2(7+w) | | -187=2-7(4x+7) | | 9l=3m | | 5(-5-3p)=-8p+3 | | 7t-(t-4)=25 | | (4a-4)(4a-1)=0 | | 0.7n+4.7=5.4n | | 5a+2a=12-15 | | -7(-3m-8)=98 | | 10-3(4x-2)=5x | | 4x-9=2x+1 | | 10x-7=5(x+1) | | 4x-29.2=7.5x-6.8 | | 3g-21=20+2g | | 5n=20(4+0.25) | | (X+2)(x^2-1)=0 | | 7685=345-5d | | -51z=-11.73 | | 2243+5754+789= | | 14*(3/2+x)=28 | | x^2+2r-360=0 | | 6x^2-22x-20=0 | | 14(3/2+x)=28 |